Russian conservatism: outlines of a responsible political course - A. P. Vorobev (Вестник университета, 2022)
The article deals with the development of conservatism in modern Russian society. The current socio-political situation indicates that Russian society refuses to accept liberal Western values, giving preference to values of a conservative nature. There is an obvious demand for conservative projects to consider the values of social justice, the greater social orientation of the state, the rules and orders that are significant for people and have been with them for decades. The Russian elites are still poorly aware of the possibilities of reflecting such a request and remain within the framework of their usual ideological and conceptual approaches. The article outlines the main problem areas of Russian conservatism, which include the lack of a conservative view on the economy, a certain degree of closeness of conservatism to society, and an upset balance between renewal and preservation. Modern Russia needs to develop a new traditionalist-conservative doctrine as a possible methodology for the development of the entire Russian society, a new, broader, Russian conservatism. It is necessary to develop own “language”, taking into account civilizational, cultural and socio-historical features.